Two Sagas from New Iceland: Reference and Allusion in Gimli Saga and Icelandic River Saga - McGillivray, Andrew; Brown-Terry, Ella J. (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2025)
When Manitoba’s Icelandic settler community composed its local history books two of the titles included the term saga: Gimli Saga (1975), authored by The Gimli Women’s Institute, and Icelandic River Saga (1985), authored by local historian Nelson Gerrard. By using the term saga, these local histories are set within and evoke an extended Icelandic historiographical tradition. This article introduces the Icelandic saga as a literary form and surveys the history and practice of local history writing, focusing particularly on the genre’s significance in Canada. The central argument draws on a comparison between select episodes from the so-called Vínland sagas (Groenlendinga saga and Eiríks saga rauða) with scenes from Gimli Saga and Icelandic River Saga, the latter selected for their apparent textual references and allusions to the aforementioned medieval sagas.